Clonal relatedness of enterotoxigenic Escherichia coli (ETEC) strains expressing LT and CS17 isolated from children with diarrhoea in La Paz, Bolivia. - Claudia Rodas (PLoS ONE, 2011)
BACKGROUND: Enterotoxigenic Escherichia coli (ETEC) is a major cause of traveller's and infantile diarrhoea in the developing world. ETEC produces two toxins, a heat-stable toxin (known as ST) and a heat-labile toxin (LT) and colonization factors that help the bacteria to attach to epithelial cells. METHODOLOGY/PRINCIPAL FINDINGS: In this study, we characterized a subset of ETEC clinical isolates recovered from Bolivian children under 5 years of age using a combination of multilocus sequence typing (MLST) analysis, virulence typing, serotyping and antimicrobial resistance test patterns in order to determine the genetic background of ETEC strains circulating in Bolivia. We found that strains expressing the heat-labile (LT) enterotoxin and colonization factor CS17 were common and belonged to several MLST sequence types but mainly to sequence type-423 and sequence type-443 (Achtman scheme). To further study the LT/CS17 strains we analysed the nucleotide sequence of the CS17 operon and compared the structure to LT/CS17 ETEC isolates from Bangladesh. Sequence analysis confirmed that all sequence type-423 strains from Bolivia had a single nucleotide polymorphism; SNP(bol) in the CS17 operon that was also found in some other MLST sequence types from Bolivia but not in strains recovered from Bangladeshi children. The dominant ETEC clone in Bolivia (sequence type-423/SNP(bol)) was found to persist over multiple years and was associated with severe diarrhoea but these strains were variable with respect to antimicrobial resistance patterns. CONCLUSION/SIGNIFICANCE: The results showed that although the LT/CS17 phenotype is common among ETEC strains in Bolivia, multiple clones, as determined by unique MLST sequence types, populate this phenotype. Our data also appear to suggest that acquisition and loss of antimicrobial resistance in LT-expressing CS17 ETEC clones is more dynamic than acquisition or loss of virulence factors.